The classical drawing atelier : a contemporary guide to traditional studio practice - Aristides, Juliette (New York : Watson-Guptill Publications, 2006)
"Ateliers have produced the greatest artists of all time?and now that educational model is experiencing a renaissance. These studios, a return to classical art training, are based on the nineteenth-century model of teaching artists by pairing them with a master artist over a period of years. Students begin by copying masterworks, then gradually progress to painting as their skills develop. Classical Drawing Atelier is an atelier in a book?and the master is Juliette Aristides, a classically trained artist. On every page, Aristides uses the works of Old Masters and today?s most respected realist artists to demonstrate and teach the principles of realist drawing and painting, taking students step by step through the learning curve yet allowing them to work at their own pace. Unique and inspiring, Classical Drawing Atelier is a serious art course for serious art students."-- from publisher's website.
-- A historical perspective : artistic training in the twenty-first century -- Design : nature and the golden ratio -- Line : two-dimensional dynamics -- Value : the world in black and white -- Form : the third dimension -- Master copy drawing : learning from the past -- Cast drawing : lessons from master sculptors -- Figure drawing : man as the measure -- Portrait drawing : window to the soul -- Atelier disciplines : finite principles, infinite applications -- Sphere drawing -- Master copy drawing -- Reductive figure drawing -- Portrait drawing.
Includes bibliographical references (page 143) and index.
Keywords: Drawing -- Technique